Women's empowerment and reducing the gender gap through digital levers - de Grimani, Lucia (Community Notebook. People, Education and Welfare in the Society 5.0, 2022)
Gender equality should not be confused with an algebraic issue, because it is in fact a cultural issue, a fundamental human right, and it is only through culture and the recognition of rights that it is possible to generate the conditions for living in a prosperous, sustainable and peaceful world. The good news is that, globally, the issue is high on many political agendas, so much so that the achievement of gender equality and the empowerment of all women is one of the 17 Sustainable Development Goals that states have committed to achieve by 2030. The bad news is that, so far, no EU Member State has achieved gender equality. The problem, therefore, is rather complex, not easy to solve, and inevitably requires reading from different perspectives. One of these is certainly what Linda Laura Sabbadini suggests in her quotation, i.e. to refer to women's empowerment. Women's empowerment is a complex socio-economic phenomenon that represents an essential step on the path towards achieving gender equality. But what is female empowerment in essence, what is it determined by, how can it be achieved and what is the situation in Italy today?